Análisis del potencial eólico y solar para la implementación de un sistema híbrido de generación eléctrica de carga unifamiliar de 800w en la comunidad de Uñacallo - Pansache provincia de Cotopaxi en el periodo 2016 - Beltran Calvopiña, Juan Carlos (2016)
The use of wind-solar energy has grown significantly in recent decades because of its environmental and economical advantages and thus it avoids global warming responsibly. This project focuses on the analysis of wind-solar, the research has used some tools for data collection and selection of potential elements to generate electricity. This system uses natural resources (wind and solar radiation) and demonstrates the mechanical conversion energy methods into electricity.